2018
DOI: 10.1097/inf.0000000000001866
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders, Antiretroviral Medication Adherence and Viremia in a Cohort of Perinatally HIV-Infected Adolescents and Young Adults

Abstract: Addressing psychiatric disorder and SUD among PHIV+ AYA may improve ART adherence outcomes in this population. Targeted interventions should be developed and tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
(41 reference statements)
5
24
0
1
Order By: Relevance
“…48 Early identification of these youth is critical for preventing the development of serious MH conditions, which may precipitate high-risk behaviors, including substance abuse and condomless sex leading to HIV transmission, as well as nonadherence to HIV treatment regimens and care for youth with PHIV. [49][50][51][52] Our data support the provision of multi-level, evidenceinformed prevention and interventions that appreciate the dynamic nature of adolescence and recognize both individual and family risk factors as key targets for prevention/intervention services. Although some community and structural stressors are not easily modified, they must be recognized and preempted through mental healthcare, recognition and de- a Adjusted OR of MH disorder for participant with a specific characteristic compared to the reference group.…”
Section: Mental Health In Us Youth With Hivsupporting
confidence: 54%
“…48 Early identification of these youth is critical for preventing the development of serious MH conditions, which may precipitate high-risk behaviors, including substance abuse and condomless sex leading to HIV transmission, as well as nonadherence to HIV treatment regimens and care for youth with PHIV. [49][50][51][52] Our data support the provision of multi-level, evidenceinformed prevention and interventions that appreciate the dynamic nature of adolescence and recognize both individual and family risk factors as key targets for prevention/intervention services. Although some community and structural stressors are not easily modified, they must be recognized and preempted through mental healthcare, recognition and de- a Adjusted OR of MH disorder for participant with a specific characteristic compared to the reference group.…”
Section: Mental Health In Us Youth With Hivsupporting
confidence: 54%
“…Another large review and meta-analysis that synthesized 125 studies with a total of 19 016 patients across 38 countries found that self-reported depression and alcohol and other substance misuse were among the top 15 barriers to adherence, along with other reasons such as forgetting, being busy, a change in routine, and the experience of medication side effects [76]. In perinatally infected youth, for whom nonadherence to treatment across health conditions is a significant issue [77], a range of psychiatric disorders, not just mood disorders, have been associated with nonadherence to HIV treatment and elevated viremia [78].…”
Section: Mental Health Impairment and Outcomes Along The Hiv Care Casmentioning
confidence: 99%
“…In the United States, anxiety and depression are among the most common mental health disorders for adolescents and young adults [34]. For HIV-positive youth, anxiety and depression have been associated with poorer medication adherence and decreased viral suppression [35-40]. Furthermore, direct and indirect relationships between depression and anxiety and increased sexual risk behaviors among youth have been identified in several studies [41], though other studies have found null or conflicting findings.…”
Section: Resultsmentioning
confidence: 99%